Business Opportunity: Sahajidah Hai-O Marketing Sdn. Bhd. / Muhamad Syamir Saifulizan - Saifulizan, Muhamad Syamir (2021)
Alhamdulillah all praises to ALLAH S.W.T because with His grace I can complete the task given in the time that has been set and be able to produce it with high quality. I would also like to express my highest appreciation to my lecturer, Nur Hazelen binti Mat Rusok who is willing to teach me so that I can produce this individual assignment. This research was made by me focusing on Sahajidah Hai-O Marketing SDN. BHD. The company was founded in the year in 1992 by Mr Tan Kai Hee as a subsidiary of Hai-O Group of Companies. Throughout the years, they have provided a platform for local entrepreneurs to grow and flourish into successful business owners and leaders. With a diverse, high quality product mix ranging from healthcare to household products, beauty products and our long renowned wellness product series, Sahajidah Hai-O Marketing is one of the leading local multi-level direct selling companies in Malaysia. Next, data collections method that I use is by searching via internet. The data in this research are valid and correct. Unfortunately for me I cannot run an interview session with one of Sahajidah Hai-O Marketing SDN. BHD. employees because of the global pandemic that arises has affected type of learning from face to face to Online Distance Learning (ODL). Thus, every unnecessary movement will be limited including travelling interstate without having a solid reason. Last but not least, in this research will explain more about before, after and my experience that I gained doing this business opportunity activity. Before activity will be explained using 5W1H method that is consist of what, why, who, when, where, and how also any other info that is relevant will be added into this research. After activity will explain on the activity that have been carried out such as how many are sold and how many customers. Then, experiential learning is about experienced that I gained after doing this activity.